Day 3 Embryo Morphology is a Significant Predictor of Blastocyst Euploidy - Yunhao Liang; Zhanhui Ou; Zhiheng Chen (IMR Press, 2023)
Background: This retrospective cohort study aims to determine the relationship between morphologic grading of day 1 or 3 embryos and euploid blastocyst rate in the preimplantation genetic testing cycle. Methods: 2001 two pronucleus (2PN) embryos were obtained from 219 patients in our in vitro fertilization center on day 1. Embryo morphologic grading was conducted on day 1 and day 3. A blastocyst trophectoderm biopsy was conducted on day 5 or day 6, followed by aneuploid screening using next a generation sequencing platform. Chi-square test, Student's t-tests and Mann-Whitney U tests were used to compare categorical and continuous variables between the cohorts. Logistic regression analysis for euploidy was conducted to determine the association of embryo morphological grading with blastocyst euploidy. Results: 811 blastocysts selected from 2001 2PN embryos were appropriate for biopsy and DNA from all biopsies were successfully amplified for aneuploidy screening. The day 1 pronuclear pattern showed a weak, non-statistically significant association with euploid blastocyst (p > 0.05). In contrast, day 3 cleavage-stage embryo scoring, which included blastomere number (p < 0.01, odds ratio (OR) = 1.156), symmetry (p < 0.01, OR = 0.710) and fragmentation (p < 0.01, OR = 0.624) all showed significant association with euploid blastocyst. 8 cell or ≥12 cell embryos were measured with the highest euploid rate, while increased blastomere size differences and fragmentation decreased the euploid embryo rate. Conclusions: Day 3, but not day 1, embryo morphology was a significant predictor for euploid blastocysts. Day 3 morphology provides individualized, visualized, and prognostic information concerning the euploid nature of a blastocyst. Blastomeres are assigned properties when selecting day 3 embryos for implantation or blastocyst culturing; thus, the morphology of day 3 embryos provides a guide for selecting euploid embryos and improving in vitro fertilization outcomes.